Instructional leadership perspective of private schools' mission definition / Noorjamaatulurul Rashdi and Muhammad Khairulsyahmi Khamis - Rashdi, Noorjamaatulurul; Khamis, Muhammad Khairulsyahmi (2017)
The role of school leaders is not only to manage the school but also functions as instructional leaders. The effectiveness of the school depends on the school leader's instructional leadership. This study focuses on the first dimension of the instructional leadership conceptual framework. Defining a school mission is the first dimension of the framework that identify how the school leaders practicing instructional leadership to defines the school's goals. There are two constructs in this dimension. The first construct is framing the school's goals and second construct is communicating the school's goal. This study focuses on these two constructs but specifically on school's academic goals. School leaders in this study refer to principals, assistant principals, heads of department, and heads of subject. Therefore, the aims of this study are to find out on how the school leaders frame and communicate the schools' academic goals. This study was conducted on 114 teachers from private schools in Kuala Lumpur and Selangor. Gombak and Cheras were the two districts selected in Kuala Lumpur and Subang was the only district selected in Selangor. The instrument for this study is a questionnaire. The questionnaire was adopted and adapted from the instrument developed by Hallinger in 1982, and it was modified in 1990. Data were analyzed using SPSS version 20.0. Percentages, means, standard deviation and independent samples t-test were produced from the data. The results are used to investigate the significant difference of private school leaders in practicing instructional leadership to define the school's academic goals. At the end of the study it shows that the private school leaders from Kuala Lumpur and Selangor are practicing the instructional leadership to define the school's academic goals.